2023
DOI: 10.1177/20499361231154443
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of antibiotic-associated dysbiosis and approaches for its management

Abstract: Increased exposure to antibiotics during early childhood increases the risk of antibiotic-associated dysbiosis, which is associated with reduced diversity of gut microbial species and abundance of certain taxa, disruption of host immunity, and the emergence of antibiotic-resistant microbes. The disruption of gut microbiota and host immunity in early life is linked to the development of immune-related and metabolic disorders later in life. Antibiotic administration in populations predisposed to gut microbiota d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 145 publications
1
29
0
Order By: Relevance
“…Probiotic bacteria and dietary supplements can potentially prevent or reverse antibiotic-associated gut microbiota dysbiosis ( Kesavelu and Jog, 2023 ). However, a comprehensive systematic review and meta-analysis conducted by Hungarian scientists found that the results of their analysis do not support probiotic supplementation during antibiotic therapy to prevent low-diversity dysbiosis ( Éliás et al, 2023 ).…”
Section: Role Of Probiotics In the Treatment Of Leptospirosismentioning
confidence: 99%
“…Probiotic bacteria and dietary supplements can potentially prevent or reverse antibiotic-associated gut microbiota dysbiosis ( Kesavelu and Jog, 2023 ). However, a comprehensive systematic review and meta-analysis conducted by Hungarian scientists found that the results of their analysis do not support probiotic supplementation during antibiotic therapy to prevent low-diversity dysbiosis ( Éliás et al, 2023 ).…”
Section: Role Of Probiotics In the Treatment Of Leptospirosismentioning
confidence: 99%
“…It can take up to 21 days to restore bacterial diversity after antibiotic treatment. Some individuals may experience a permanent decline in microbiome diversity [ 24 ].…”
Section: Correlation Analysis and Research Perspectivesmentioning
confidence: 99%
“…However, the role of BDNF in regulating intestinal inflammation remains complex and context dependent. In vitro , BDNF protected intestinal epithelial cell lines against TNF-α and IFN-γ-induced injury [ 73 ]. The underlying mechanisms may involve inhibition of NF-κB activation and reduced expression of various proinflammatory cytokines [ 74 ], as shown in Figure 2 .…”
Section: Immunoregulatory Functions Of Bdnf In the Gutmentioning
confidence: 99%
“…In the acute setting, BDNF levels decrease in injured colonic mucosa, which impairs epithelial restitution [ 88 ]. Exogenous BDNF administration activates cytoprotective Akt signalling and prevents apoptosis in colonic epithelial cells exposed to proinflammatory cytokines [ 73 ]. These acute protective effects were lost in cells isolated from IBD mucosa with reduced TrkB receptor expression [ 89 ].…”
Section: Role Of Bdnf In the Pathogenesis Of Inflammatory Bowel Diseasementioning
confidence: 99%